Pengaruh Penggunaan Modul Berbasis Potensi Lokal pada Topik Ekosistem terhadap Pemahaman Konsep dan Sikap Peduli Lingkungan Siswa Kelas X - Muthmainah Muthmainah; Nurmiyati Nurmiyati; Sri Dwiastuti (Universitas Sebelas Maret, 2016)
The aim of this research is to know the effect of module based on local potential in ecosystem on the understanding of concept and attitude of care for environment of the X graders. This research was a quasi-experimental with design used was Nonequivalent Control-Group Design from February until May 2016. The population of research was all X gradesrs of SMA Negeri 1 Tanjungsari in the school year of 2015/2016. X-A and X-B class were selected as the sample. Data was obtained from questionairre for attitude of care environment and understanding of concepts test.. Data was analyzed with anacova-test with level of significance 0,05. The result of the research shows that (1) obtained Fa= 43,728 > F0 =4,00. (2) obtined Fb= 15,699 > F0 =4,00. Thus H0 was not supported, and H1 was supported, it means that there was a significant difference of the effect between the use of module based on local potential in ecosystem topic in experiment class and application of conventional learning model with varying lecture in control group on understanding of concepts and the students attitude of care for environment.Keywords: module based on local potential, understanding of concepts, attitude of care for environment